ANALYSIS OF DYNAMIC CHARACTERISTICS OF SPHERICAL HYBRID SLIDING BEARINGS BASED ON ORIFICE THROTTLING (MT) - CHEN YuFei; SHEN JingFeng; ZHOU YiHao (Jixie qiangdu)
Taking the spherical sliding bearings with orifice throttling as the research object, the mathematical model of lubrication of spherical hybrid sliding bearings is established and the Reynolds equation under laminar flow state is deduced from this model. The pressure distribution of the oil chamber and oil edge are calculated according to the flow conservation principle of the orifice throttle. Combining with the finite difference method and relaxation iterative method to solve the disturbance pressure control equation which is derived by means of perturbation method. The stiffness coefficient and damping coefficient of spherical sliding bearings are used to study the influence of supply pressure, rotating speed, average oil film clearance and other parameters on the dynamic characteristics coefficient of the bearing through numerical analysis. The results show that as the oil film clearance decreases and the oil supply pressure increases, the stiffness coefficient and damping coefficient will increase accordingly. As the rotating speed increases, the changing trend of the direct stiffness is small while the decreasing trend of the direct damping is obvious. When the oil film clearance is 20 μm, the stiffness coefficient and damping coefficient of spherical hybrid sliding bearings reach the maximum. The increasing of rotating speed has little effect on the stiffness while the damping coefficient will be significantly reduced.